Computational fluid dynamics simulation of rough bed open channels using openFOAM - Cho, Yun-Hang; Dao, My Ha; Nichols, Andrew (Frontiers in Environmental Science, 2022)
With increased flood risk due to climate change, population expansion and urbanisation; robust waterway design and management are critical. One common type of waterway used to gather and transport ground water is the open channel. Most simulations do not account for the physical roughness of the bed, instead using a roughness coefficient. This means that only the turbulent energy content can be modelled whilst physical turbulent eddies and vortices cannot. Furthermore, many past studies assume the free surface is a rigid lid. This could affect the way that turbulent structures near the free surface behave. Computational Fluid Dynamics simulation of an open channel with a rough bed and rigid lid are conducted using OpenFOAM. Results show good correlation with experimental tests. It can be visually observed that turbulent structures generated from the rough bed do interact with the free surface and thus a rigid lid is perhaps not a great approximation. This is supported by an apparent decrease in the Reynolds shear stress from the free surface and 30% of the flow depth immediately beneath.